An investigation into how the health care assistants perceive their role as 'support workers' to the qualified staff - Workman, B A (Journal of advanced nursing, 1996)
This qualitative study investigates the support worker's role as perceived by health care assistants (HCAs) who have undergone some training and National Vocational Qualification assessments. The findings suggest that the HCAs consider that they support the trained nurses by acting as a link in the communication chain between the patient and carers, and by providing 'time' for the trained nurse to use in therapeutic activities. The indications are that the HCAs perceive little difference between their roles and those of qualified nurses, and they experience ambiguity as to their proper role. The researcher sought to apply role theory in an inductive approach to data interpretation, from which it is posited that the HCAs' role ambiguity arises because the qualified nurses' own role lacks clarity and this affects their expectations of the HCA's role. Having had some training, the roles are more ambiguous now than before as the HCAs are no longer untrained carers but nor are they qualified professionals. It is also suggested that the qualified nurses perceive the HCAs as a threat to their own roles in that the HCAs are seen as depriving them of their 'real' nursing role; thus they are experiencing 'role deprivation'. Recommendations to clarify role expectations and reduce role ambiguities are suggested to alleviate an avoidable source of stress for both the qualified nurse and the HCA.